Between Prestige and Marginality: the III Biennial of Sculpture of the Cervecería Costa Rica - Alpízar Valverde, Nicolás (2025)
Introduction: The III Biennial of Sculpture of the Cervecería Costa Rica (III BECCR) highlighted the tensions within the Costa Rican artistic field, characterized by the confrontation between modern and contemporary paradigms. Objective: This paper aims to analyze these dynamics through a theoretical framework that includes the concepts of social fields and habitus (Bourdieu, 2008). Methods: The methodology employed consists of a review of the official catalog of the event, which serves as a basis for categorizing and extracting information about the works and participating artists. Results: The results reveal a list of works and a reflection on the subjectivities and tensions among different actors in the artistic field. Through an autoethnographic exercise, the author shares their experience as a sculpture student at that time, allowing for a critical perspective on changes observed over the years. Conclusions: The conclusions highlight the need to recognize the coexistence of both paradigms in Costa Rican art and to make visible the contributions of empirical artistic producers and the general public, who often remain marginalized in this context.